HOTS-Based Learning Versus HOTS-Based Test Instruments: A Study Analysis of Elementary School Teachers' and Students' Readiness - Isrokatun, Isrokatun; Sunaengsih, Cucun; Maulana, Maulana; Syahid, Aah Ahmad; Karlina, Dety Amelia; Rohaeti, Popon (Universitas Pendidikan Indonesia, 2024)
The research is motivated by the demands for the readiness of elementary school teachers and students to face the Merdeka Curriculum, one of which is the demand for HOTS- based learning. The implementation of HOTS-based learning requires an evaluation using HOTS- based test questions as well. The objectives are, 1) to analyze and examine the readiness of teachers in supporting the implementation of HOTS-based learning and its evaluation using HOTS-based test instruments, and 2) to analyze and examine how students' readiness to receive HOTS-based tests, especially in mathematics. This study used the survey method. The survey was conducted on 172 teachers and 154 high grade students in West Java, Indonesia. The instrument used questionnaires, for teachers distributed through Google Form, while for students using paper questionnaires that were filled in manually. Research results: 1) Elementary school teachers aren’t fully prepared to implement HOTS-based learning, there are still misconceptions of teachers' understanding of HOTS learning; 2) In Mathematics, there are still many students who aren’t ready to accept the presence of HOTS-based test questions, because they haven’t mastered basic arithmetic skills. This is the biggest obstacle for students to be able to absorb, accept, and solve HOTS-based math questions as an evaluation standard in the Merdeka Curriculum.